KERAGAMAN BENTUK DAN WARNA KEMBANG KERTAS (Zinnia elegans Jaqc.) POPULASI M6 - , ARIYANI, Dr. Ir. Aziz Purwantoro, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Zinnia elegans Jacq.has a large potential as a cut flower because it is very suitable to be cultivated in Indonesia. X-ray irradiation have been done to increased the diversity of flower Zinnia elegans Jacq. Then get selected. This study was conducted to determine the flowers diversity, shapes and colors proportions in M6 populations. This research was conducted in Krapyak, Triharjo, Sleman, Yogyakarta from March 2012 until August 2012. The flowers with character pompom and red purple color were taken from 140 plants of M4 population. This selection produced 14 plants with purple red and white color of M5 population. Seven plant numbers were selected from M5 population based on the similarity of the red purple color ray florets. The results of this open pollination seed were planted consists of 7 numbers plants, each plant consists of 2 flowers. The qualitative characters of observation variable are shapes and colors of flowers. To calculated the proportion of flowers with flower shapes or colors of a particular flowers. The results showed that there were percentage increasement of the M5 to the M6 pompom flowers from 7.1% to 13.1% and the color purple red purple from 78.5% to 81.1%. Flower color on the M6 group gained 4 colors: red purple group, group red, white and yellow group with the comparison group 81.1%: 4.8%: 9.4%: 4.5% and the ratio of single flower shape: double: pompom for 44.4%: 42.3%: 13.1%.